Questions Cooperative Directors Should Be Asking Management - Bruce L. Anderson; Brian M. Henehan (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2002)
The most important responsibility of cooperative directors is to judiciously ask the right questions of management. It has been suggested that some directors do not know all of the correct questions to ask of management, or how. The purpose of this paper is fourfold: 1) To briefly describe how directors should pose questions to management, 2) To provide an extensive list of questions directors should know the answers to, 3) To outline a generic format for asking general questions and 4) To assist in identifying important board issues and how to handle them. Certainly this is not a complete list of questions or possible director concerns. However, we hope it covers most of the important issues directors will confront in carrying out their fiduciary responsibilities. We also suggest that these questions may be used by nominating committees and members to explore the cooperative business philosophy and knowledge of director candidates. In this paper, we have not provided answers to the questions. We assume directors that are elected to cooperative boards, in some cases multi-billion dollar companies, have sufficient business knowledge and experience to know the appropriate answers.
Keywords: 330; Vorstand; Führungskräfte; Management